2010
DOI: 10.2165/11530390-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Maximal Accumulated Oxygen Deficit Method

Abstract: The maximal accumulated oxygen deficit (MAOD) method has been extensively, but unfortunately not very methodically, used; the procedure used to determine the MAOD varies considerably. Therefore, this review evaluates the effect of different numbers and durations of submaximal exercise bouts on the linear power output (PO)-oxygen uptake ((.)VO2) relationship and thus the MAOD. Changing the number and duration of the submaximal exercise bouts substantially influences the calculated MAOD when relatively long subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 72 publications
1
97
0
1
Order By: Relevance
“…The reason for this is not fully clear, but may be related to the fact that the MAOD ALT does not need an estimate of supramaximal oxygen demand compared to traditional MAOD. In fact, the supramaximal oxygen demand, and consequently MAOD, can be substantially influenced by the number, intensity, and duration of the submaximal exercise bouts [4]. In addition, an important advantage of the MAOD ALT is that it provides a separate estimate of alactic and lactic components of the AC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this is not fully clear, but may be related to the fact that the MAOD ALT does not need an estimate of supramaximal oxygen demand compared to traditional MAOD. In fact, the supramaximal oxygen demand, and consequently MAOD, can be substantially influenced by the number, intensity, and duration of the submaximal exercise bouts [4]. In addition, an important advantage of the MAOD ALT is that it provides a separate estimate of alactic and lactic components of the AC.…”
Section: Discussionmentioning
confidence: 99%
“…The AC is an important parameter for measuring athletic performance during short-distance sports such as 500–4,000 m cycling time trials [6]. While there is no “gold-standard” method to estimate AC, it has been consensually assessed by the maximal accumulated oxygen deficit (MAOD) [4]. The MAOD is calculated by the difference between the accumulated oxygen uptake during an exhaustive supramaximal test, and the corresponding predicted oxygen demand estimated from several submaximal exercise bouts [1, 3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that anaerobic processes contribute substantially [7,8] during sprint races (3-4 min) and may be highly important for performance on variable terrain [7]. Nevertheless, indirect assessments of the anaerobic energetic component during whole-body exercise is associated with some difficulties [9]. The anaerobic energetic component during supramaximal roller-skiing can be estimated in several different ways [7,8], either by using the maximal accumulated oxygen deficit method [9] or a method based on gross efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, indirect assessments of the anaerobic energetic component during whole-body exercise is associated with some difficulties [9]. The anaerobic energetic component during supramaximal roller-skiing can be estimated in several different ways [7,8], either by using the maximal accumulated oxygen deficit method [9] or a method based on gross efficiency [7]. A main problem with all previous methods employed for roller-skiing is that they have excluded the influence of instantaneous changes in inertia on the power output estimates during self-paced, timetrial roller-skiing [7,8].…”
Section: Introductionmentioning
confidence: 99%